The Influence of Work Life Balance and Psychological Empowerment on Innovative Work Behavior Mediated by Employee Engagement on Employees of PT Sinar Sosro Tbk, Medan City - Rafiqah, Fathyah Sauma; Khair, Hazmanan (AMAR (Andalas Management Review), 2025)
This study aims to determine: (1) The effect of work life balance, Work life Balance, Psychological Empowerment dan Employee Engagement on innovative work behavior in employees of PT Sinar Sosro Tbk. Kota Medan. This research is associative research using a quantitative approach. The population of this study were 103 employees of PT. Sinar Sosro Tbk. Medan City with saturated sampling purposive. Data collection using a questionnaire. Data processing in this study using the PLS (Partial Least Square) 4.0 software program the data collection techniques used in this study are questionnaires (questionnaires), interviews, in analyzing the data and information needed, the authors use data analysis techniques including measurement models (outer model), namely reliability and construct validity; and (b) discriminant validity. (2) structural model analysis (inner model), namely (a) coefficient of determination (R-square); (b) F-square; (c) hypothesis testing, namely (1) direct effect; (2) indirect effect.